Analysis of Indonesian Language Errors in Student Practicum Reports - Sinaga, Merry Christina; Anastasia, Yulita; Daulay, Adrian; Marbun, Ari Andani; Hazrian, Al Fari; Siallagan, Lasenna (Jurnal Ilmiah Pendidikan Holistik (JIPH), 2024)
The aim of this research is to analyze the use of diction and sentence writing in practical reports made by students of the Physics Study Program at Medan State University. This study involved PSF A 2022 students from Medan State University. The research method used is qualitative descriptive research by analyzing the contents of a sample of student practicum reports. Data was collected by reviewing practicum results reports and interviewing a number of students to determine the factors that caused errors in letters, words, punctuation and phrases in their papers and practicum reports. Next, the data was validated using triangulation techniques and informant evaluation through interactive analysis which consisted of four stages: data collection, data reduction, data delivery, and drawing conclusions or verification.